Characterization of volatile compounds from three Cymbopogon Species and Eucalyptus citriodora from Benin and their insecticidal activities against Tribolium castaneum - BOSSOU, ANNICK FLORE ARLETTE DOHOUÉ; DAHOUENON-AHOUSSI, Edwige (My University, 2015)
tThe chemical volatile profiles of four plant species from Benin were established via SDE/GC–MS andSPME/GC–MS, and were compared to chemical profiles obtained by hydrodistillation/GC–MS. Essentialoils and selected identified compounds were used to perform fumigant tests and contact “no choice”tests against adults of the red flour beetle Tribolium castaneum, an important pest insect in stored prod-ucts worldwide. The chemical profiles and the concentrations of the main compounds varied with themethod used. Geranial (hydrodistillation, SPME) and geraniol (SDE) for Cymbopogon citratus, piperitonefor Cymbopogon schoenanthus (hydrodistillation, SPME, SDE), E-p-mentha-1(7), 8-dien-2-ol for Cymbo-pogon giganteus (hydrodistillation, SPME, SDE), neo-isopulegol (SDE) and citronellal (hydrodistillationand SPME) for Eucalyptus citriodora, were identified as main volatile compounds. By fumigation, the LC50values obtained after 24 h for essential oils of C. citratus, C. giganteus, C. schoenanthus, E. citriodora, andfor piperitone and citronellal were 4.2 mL/L air, 2.3 mL/L air, 2.1 mL/L air, 2.0 mL/L air, 0.5 mL/L air and1.2 mL/L air, respectively. Furthermore, mortalities of 100%, 82%, 75%, 72%, 68% and 42%, respectively,were found for piperitone at 2.4 mL/L air, citronellal at 2.1 mL/L air, and essential oil extracted from E.citriodora, C. schoenanthus, C. giganteus and C. citratus, at 4 mL/L air. By contact “no choice” test, the LC50values for the crude oils after 72 h were: 15% (w/v), 6% (w/v), 6% (w/v) and 5% (w/v) for C. citratus, C.giganteus, C. schoenanthus and E. citriodora, respectively. After 72hours, mortalities of 18%, 67%, 73%, 82%,87% and 40% for essentials oils (8% w/v) of C. citratus, C. giganteus, C. schoenanthus, E. citriodora, piperitoneat 4.7% w/v, and citronellal at 4.2% w/v, respectively, were obtained. The essential oil from C. schoenanthusand E. citriodora as well as piperitone and citronellal represent potential valuable alternative pesticidesto conquer the resistance of T. castaneum to synthetic insecticides.
Keywords: SPME; SDE; Chemical volatile profiles; Contact “no choice” test; Fumigant test; Tribolium castaneuma